Puss Caterpillar (Larva), Southern Flannel Moth (Adult), Megalopyge opercularis (J. E. Smith 1797) (Insecta: Lepidoptera: Zygaenoidea: Megalopygidae) - Donald W. Hall (EDIS)
The southern flannel moth is an attractive small moth that is best-known because of its larva, the puss caterpillar, which is one of the most venomous caterpillars in the United States. This 12-page fact sheet was written by Donald W. Hall and published by the UF Department of Entomology and Nematology, January 2013.